Inhibition of Aberrant IGF-I Signaling in Diabetic Male Rat Retina Prevents and Reverses Changes of Diabetic Retinopathy - Gang Xi; Christine Wai; David Clemmons (Journal of Diabetes Research)
Hyperglycemia results in inhibition of cleavage of integrin-associated protein (IAP) thereby allowing it to bind to SHPS-1 which results in pathophysiologic changes in endothelial function. This study determined if an anti-rat IAP antibody directed against the SHPS-1 binding site which disrupts IAP/SHPS-1 association could inhibit these pathophysiologic changes. The anti-IAP antibody inhibited IGF-I-stimulated SHPS-1, p52Shc, MAP kinase phosphorylation, and proliferation in endothelial cells. To determine if it could reverse established pathophysiologic changes in vivo, this antibody or normal rat IgG F(ab)2 was injected intraperitoneally for 6 weeks into rats that had diabetes for 4 weeks. Optical coherence tomography (OCT) showed that retinal thickness increased at 4 weeks and this increase was maintained in rats treated with the control antibody for an additional 6 weeks. The increase was reversed by anti-IAP antibody treatment (84.6±2.0 compared to 92.3±2.5 μm, p<0.01). This value was similar to nondiabetic animals (82.2±1.6 μm, p, NS). The anti-IAP antibody also decreased retinal vascular permeability (0.62±0.12 vs. 0.96±0.25%/g/h, p<0.001). To determine if it was effective after local injection, this antibody or control was administered via intravitreal injection. After 3 weeks, retinal thickness increased to 6.4±2.8% in diabetic rats, and IAP antibody treatment prevented this increase (0.8±2.5%, p<0.01). It also prevented the increase of retinal vascular permeability (0.92±0.62 vs. 1.63±0.99%/g/h, p<0.001). Biochemical analyses of retinal extracts showed that the anti-IAP antibody inhibited IAP/SHPS-1 association and SHPS-1 phosphorylation. This resulted in inhibition of AKT activation and VEGF synthesis in the retina: changes associated with increased vascular permeability. We conclude the anti-rat IAP antibody disrupts IAP/SHPS-1 association and attenuates aberrant IGF-I signaling thereby preventing or reversing the progression of retinal pathophysiological changes.